ERBB family fusions are recurrent and actionable oncogenic targets across cancer types - Schubert, Laura; Elliott, Andrew; Le, Anh T.; Estrada-Bernal, Adriana; Doebele, Robert C.; Lou, Emil; Borghaei, Hossein; Demeure, Michael J.; Kurzrock, Razelle; Reuss, Joshua E.; Ou, Sai-Hong Ignatius; Braxton, David R.; et al. (Frontiers in Oncology, 2023)
Purpose: Gene fusions involving receptor tyrosine kinases (RTKs) define an important class of genomic alterations with many successful targeted therapies now approved for ALK, ROS1, RET and NTRK gene fusions. Fusions involving the ERBB family of RTKs have been sporadically reported, but their frequency has not yet been comprehensively analyzed and functional characterization is lacking on many types of ERBB fusions. Materials and Methods: We analyzed tumor samples submitted to Caris Life Sciences (n=64,354), as well as the TCGA (n=10,967), MSK IMPACT (n=10,945) and AACR GENIE (n=96,324) databases for evidence of EGFR, ERBB2 and ERBB4 gene fusions. We also expressed several novel fusions in cancer cell lines and analyzed their response to EGFR and HER2 tyrosine kinase inhibitors (TKIs). Results: In total, we identified 1,251 ERBB family fusions, representing an incidence of approximately 0.7% across all cancer types. EGFR, ERBB2, and ERBB4 fusions were most frequently found in glioblastoma, breast cancer and ovarian cancer, respectively. We modeled two novel types of EGFR and ERBB2 fusions, one with a tethered kinase domain and the other with a tethered adapter protein. Specifically, we expressed EGFR-ERBB4, EGFR-SHC1, ERBB2-GRB7 and ERBB2-SHC1, in cancer cell lines and demonstrated that they are oncogenic, regulate downstream signaling and are sensitive to small molecule inhibition with EGFR and HER2 TKIs. Conclusions: We found that ERBB fusions are recurrent mutations that occur across multiple cancer types. We also establish that adapter-tethered and kinase-tethered fusions are oncogenic and can be inhibited with EGFR or HER2 inhibitors. We further propose a nomenclature system to categorize these fusions into several functional classes.